2006
DOI: 10.1086/505525
|View full text |Cite
|
Sign up to set email alerts
|

The Mass of the Central Black Hole in the Seyfert Galaxy NGC 4151

Abstract: In order to improve the reverberation-mapping based estimate of the mass of the central supermassive black hole in the Seyfert 1 galaxy NGC 4151, we have reanalyzed archival ultraviolet monitoring spectra from two campaigns undertaken with the International Ultraviolet Explorer. We measure emission-line time delays for four lines, C IV 1549, He II 1640, C III] 1909, and Mg II 2798, from both campaigns. We combine these measurements with the dispersion of the variable part of each respective emission line to ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 33 publications
10
126
0
Order By: Relevance
“…Even though the International Ultraviolet Explorer (IUE ) data set of Clavel et al (1990) is undersampled and the IUE data set of Ulrich & Horne (1996) is of a fairly short duration, the estimate of M BH determined by Metzroth et al (2006) of (4:14 AE 0:73) ; 10 7 M is in good agreement with the value we obtain above. Figure 3 shows the lag and line-width measurements (given by cen and lin ) for NGC 4151 from Metzroth et al (2006) and from this work. We fit a power law to the UV data from Metzroth et al (2006) and the optical data from this work.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Even though the International Ultraviolet Explorer (IUE ) data set of Clavel et al (1990) is undersampled and the IUE data set of Ulrich & Horne (1996) is of a fairly short duration, the estimate of M BH determined by Metzroth et al (2006) of (4:14 AE 0:73) ; 10 7 M is in good agreement with the value we obtain above. Figure 3 shows the lag and line-width measurements (given by cen and lin ) for NGC 4151 from Metzroth et al (2006) and from this work. We fit a power law to the UV data from Metzroth et al (2006) and the optical data from this work.…”
Section: Discussionsupporting
confidence: 83%
“…Figure 3 shows the lag and line-width measurements (given by cen and lin ) for NGC 4151 from Metzroth et al (2006) and from this work. We fit a power law to the UV data from Metzroth et al (2006) and the optical data from this work. Even with the small range of values available for and ÁV , we find that the best fit gives a slope of ¼ À0:76 AE 0:24, consistent with the slope of ¼ À0:5 expected if the virial relationship between the size of the BLR and the velocity of the gas exists.…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas C iv reverberation studies of a handful of objects are consistent with expectations from Hb (Peterson et al 2005), a clear indication of reverberation has not yet been found for Mg ii. Although the line has been seen to vary in both flux and width (e.g., Clavel et al 1991;Dietrich & Kollatschny 1995;Metzroth et al 2006;Woo 2008), only weak Mg ii reverberation signals have been seen (Reichert et al 1994). Thus, the mass relation for Mg ii relies on the correlation of single-epoch estimates with Hb masses and the argument that Mg ii and Hb have similar ionization potentials (McLure & Dunlop 2004).…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Reverberation mapping studies of Mgiiλ2800 are not yet conclusive, and they leave open the possibility that the average emitting distance of Mgiiλ2800 is larger than for Hβ (Metzroth et al 2006;Trevese et al 2007;Woo 2008). In addition to the theoretical considerations of Sect.…”
Section: Mgiiλ2800 Virial Broadening and Virial Productmentioning
confidence: 98%